Case report: Microsatellite instability-high pancreas adenosquamous carcinoma with postoperative liver metastasis recurrence treated with multimodality therapy achieving complete pathological response - Liu, Qinghua; Li, Ruoyun; Zhu, Wei; Zheng, Pengfei (Frontiers in Immunology, 2024)
Pancreatic adenosquamous carcinoma (PASC) is a rare subtype of pancreatic cancer (PC), with no established consensus on the optimal treatment for postoperative liver metastasis recurrence. We report a case of a 48-year-old male patient who underwent radical surgery and was pathologically diagnosed with microsatellite instability-high (MSI-H) PASC. The patient experienced liver metastasis recurrence following single-agent gemcitabine adjuvant chemotherapy. After one session of transarterial chemoembolization (TACE) with oxaliplatin, fluorouracil, and epirubicin, followed by six cycles of adjuvant chemotherapy with gemcitabine and nab-paclitaxel combined with sintilimab immunotherapy and bevacizumab targeted therapy, complete pathological regression of the liver metastasis was achieved. The patient has now reached a 24-month survival period and continues to be monitored at our center. This case illustrates the promise of the proposed treatment regimen, highlighting the significant potential of multimodality strategies in managing metastatic recurrence of MSI-H PASC.